(3JbGSje GdYdds - (3eMeO Hf RcQjG GdnqQGRj, CHh HcQ,J (B311 (3g` s
(3ChdgG (B:s
(3HGHG ai OB GdKYdH hHhegG jdhW GdTYQ jchf Pdc ef HdZe eMJQb Gddhf hYdGeJg Cf jchf UGMHg CHjV Gddhf YHd GdHOf CRYQ GdLdO hjchf bO CcKQ ef EcKGQ GdCZPjI GdHGQOI hGdQWHI s
(3BNQgG (B:s
(3eHJhQ , jfJgi GdehLhO efgG CKfGA HGH ai GdLOQi hGdMUHI , Hbhdg (B: (3hEf hLOJ GdMcI GdJi ai GdYjf dG JScf Ydi Pdc , Hd JYGhO HGTO eeG cGfJ abWQ ajgG s
(3fSNI KGfjIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfi (B- (3U (B63 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdWHs